1976
DOI: 10.1016/0304-3959(76)90047-6
|View full text |Cite
|
Sign up to set email alerts
|

Illness behaviour syndromes associated with intractable pain

Abstract: One hundred patients, referred for the management of intractable pain, completed a 52-item Illness Behaviour Questionnaire (IBQ). Responses were scored on 7 scales: general hypochondriasis, disease conviction, psychological versus somatic perception of illness, affective inhibition, affective disturbance, denial, and irritability. IBQ scale profiles were subjected to numerical analysis and 6 taxonomic clusters were identified. Patients in groups 1-3 were characterized by a relatively non-neurotic, reality-orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

1983
1983
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Pilowsky and Spence [28] noted that pain patients reject the suggestion that their pain is psychological and report difficulty in expressing feelings. Blumer and Heilbronn [29] observed that chronic pain patients typi cally display alexithymie characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Pilowsky and Spence [28] noted that pain patients reject the suggestion that their pain is psychological and report difficulty in expressing feelings. Blumer and Heilbronn [29] observed that chronic pain patients typi cally display alexithymie characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In such a developmental context pain is utilized as a masochistic symptom to ward off abandonment. From a behavioral perspective, the chronic pain patient 'learns' to give in to chronic pain since he is allowed the sick role and absolved from normal duties [62] , Financial compensation reinforces this behavior. Analgesic medication given on de mand further reinforces a passive coping style.…”
Section: The Chronic Pain Patientmentioning
confidence: 99%
“…The IBQ [12] is a 62 item self-report instrument which delineates illness behaviour, particularly those aspects related to inappropriate or maladaptive modes of responding to illness. It was devised initially on a pain clinic population [ 12] but it has since been used with rheumatology, cardiovascular and family prac tice patients, and it has also been used as a screening instrument [11].…”
Section: Instrumentsmentioning
confidence: 99%
“…It was devised initially on a pain clinic population [ 12] but it has since been used with rheumatology, cardiovascular and family prac tice patients, and it has also been used as a screening instrument [11]. It provides 7 scales: general hypo chondriasis, disease conviction, psychological versus somatic perception of illness, affective inhibition, dys phoria, denial and irritability.…”
Section: Instrumentsmentioning
confidence: 99%